The contingent role of state capacity on the impact of e-government on environmental sustainability in developing countries - Banda, Lloyd George; Du Plessis, Davy Julian (Frontiers in Political Science, 2024)
E-government is a prominent approach in environmental sustainability as it brings various arrangements that allow for the mitigation of greenhouse gas emissions. The article explores two main objectives. Firstly, the direct impact of e-government on ecological sustainability and secondly, whether e-government enhances environmental sustainability indirectly by improving state capacity. By understanding this nexus, we believe that states in LDCs will seek to explore the maximum potential benefits of ICTs in government operations to establish a more responsive, open, and people-oriented government. The paper utilizes a balanced macro-panel sample of 45 United Nations classified least developed countries from 2003 to 2022. To ensure the reliability of empirical findings, three econometric methods—system generalized methods of moments (GMM), instrumental variable GMM (IV-GMM), and bootstrap ordinary least squares (BOLS) are employed. The results of the entire sample model reveal several key findings. These findings are that e-government development has a direct and positive impact on environmental sustainability, secondly state capacity negatively influences ecological sustainability, and lastly e-government development indirectly affects environmental sustainability by enhancing state capacity. Additionally, intriguing sub-sample findings for least developed countries in Africa and Asia are observed, with notable lessons from the latter, where environmental performance is improving at the expense of a high volume of carbon emissions. However, these overall findings underscore the importance of considering how governments can address environmental sustainability requirements by managing e-government programs and enacting responsible ICT-enabled transformations.